Estrogen affects the negative feedback loop of PTENP1-miR200c to inhibit PTEN expression in the development of endometrioid endometrial carcinoma. Issue 1 (2018) - Chen, Ruichao; Zhang, Minfen; Liu, Wenya; Chen, Hui; Cai, Tonghui; Xiong, Hanzhen; Sheng, Xiujie; Liu, Shaoyan; Peng, Juan; Wang, Fang; Chen, Hao; Lin, Wanrun; et al.
Abstract Endometrial carcinoma is one of the most common malignancies in the female reproductive system. It is well-known that estrogen plays an important role in the pathogenesis of endometrioid endometrial carcinoma (EEC), and induces the cancer suppressor gene PTEN deletion. However, how estrogen affects PTEN expression remains unknown. In the present study, we found in 40 EEC specimens, miR-200c level was higher in most cancer areas than that in the adjacent normal endometrium, while PTEN and PTENP1 were lower. Moreover, the expression of PTEN/PTENP1 and miR-200c also showed a converse relationship in EEC cell lines. In addition, we demonstrated that miR-200c bound directly to PTEN and PTENP1, and PTENP1 could reverse miR-200c inhibition function to PTEN using a dual-luciferase reporter and RNA binding protein immunoprecipitation (RIP) assays. Next, 17β-estradiol (E2) treatment could improve miR-200c and drop the PTEN level, which caused a consequential increase of the phospho-PI3K-AKT pathway genes. When we stably knocked down estrogen receptor α (ERα) expression in the EEC cell line, the effects of E2 on miR-200c and PTEN declined. In addition, it was demonstrated that E2 might modulate cell proliferation, migration and invasion relying on the expression of miR-200c. Taken together, it can be concluded that estrogen improves the miR-200c level by combining with ER, PTENP1 and PTEN could be inhibited by miR-200c, and then activate the PI3K-AKT pathway. This work provided a new mechanism of EEC development and a new potential therapeutic target.